Multidisciplinary Care of the Head and Neck Cancer Patient (Cancer Treatment and Research,, 2018)
This book identifies key treatment challenges and unique care considerations in patients with head and neck cancers, providing a comprehensive guide to patient management that illustrates the critical importance of a multidisciplinary approach in achieving optimal oncological, functional, and survival outcomes. It covers all relevant specialties, including dental and oral medicine, medical oncology, radiation oncology, surgical oncology, and reconstructive surgery. It highlights the vital role played by ancillary head and neck cancer services, such as speech and swallowing therapy, occupational and physical therapy, and nutritional therapy in offering essential physical and psychological support from the time of diagnosis onward. The closing chapters address post-treatment issues, including those relating to survivorship, surveillance, and end-of-life care. Multidisciplinary care is perhaps even more important for patients with head and neck cancers than for other cancer patients, and in addressing all its aspects this book is invaluable for a wide range of practitioners.